KAJIAN TENTANG PENGEMBANGAN PROFESI GURU DALAM KOMPETENSI PEDAGOGIK MELALUI PENAMBAHAN PENDEKATAN PADA KURIKULUM MERDEKA - Pane, Agnes; Sembiring, Elvina Br; Harianja, Lusi; Yopi, Mhd. Hafiz Fahrezy; Simanjuntak, Novita Sarah Simanjuntak; Siboro, Ervina Sumiati (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
Improving the quality of education depends on developing teachers' pedagogical competence and implementing a curriculum that suits the needs of students. A flexible and innovative curriculum allows teachers to adapt more effective learning methods, one of which is through the Deep Learning approach. This approach aims to increase students' in-depth understanding, build critical thinking skills, and encourage active involvement in the learning process. This study aims to identify the effectiveness of implementing the Deep Learning approach in improving student learning outcomes at SMP Negeri 29 Medan. The research method used is descriptive qualitative with data collection techniques through in-depth interviews with educators and professionals. The results show that curriculum flexibility and innovative methods contribute to creating a more interactive and meaningful learning environment. However, challenges such as limited facilities, educators' readiness, and conventional evaluation systems still require further attention. Hopefully, the results of this study can encourage the implementation of more effective and sustainable learning strategies. The implication of this research is the need for support from various parties to realize education that is adaptive and responsive to the times.